A Review on Coverage Optimization in Heterogeneous Network - Mehta, Priya; Singh, Sujeet; Ali, Syed Imran (International Journal of Computer Sciences and Engineering, 2025)
Smart and flexible wireless devices brings with them, associate degree ever continued challenge of finding economical suggests that for resource usage. Scope and avenues for capability and coverage improvement in cellular networks area unit perpetually explored. Readying of little cells like microcells, picocells, hotspots, and relays established a good answer to enhance network coverage and capability. However, this will increase in performance occurs with the price of preparation and maintenance of extra base stations. Another fascinating answer to enhance coverage and network capability is that the use of user instrumentality with relaying support.